10 gram-scale synthesis of a chiral oxazoline iminopyridine ligand and its applications. Issue 2 (31st October 2017) - Chen, Jianhui; Xi, Tuo; Lu, Zhan
Abstract : This method reports on the preparation of a chiral oxazoline iminopyridine (OIP) ligand and its applications on a scale of 10 grams. Abstract : This method reports on the preparation of the chiral oxazoline iminopyridine (OIP) ligand and its applications in the asymmetric hydroboration and hydrosilylation of 1, 1-disubstituted alkenes. These reactions could be carried out on a scale of 10 grams.